A comparison study of clinician‐rated atopic dermatitis outcome measures for intermediate‐ to dark‐skinned patients. (1st March 2017) - Zhao, C.Y.; Hao, E.Y.; Oh, D.D.; Daniel, B.S.; Martin, L.K.; Su, J.C.; Rodrigues, M.; Murrell, D.F.
Summary: Background: Atopic dermatitis (AD) assessment is more difficult in patients with skin of colour (SOC). Objectives: To compare the reliability of commonly used outcome measures for assessing AD in patients with SOC and to evaluate a novel greyscale in this population. Methods: Twenty‐five patients with AD each attended a 1‐day scoring exercise based in either Sydney or Melbourne, Australia. Each patient was scored by the same five physicians using the Eczema Area and Severity Index (EASI), objective Scoring Atopic Dermatitis (oSCORAD), Investigator's Global Assessment (IGA) and a novel greyscale. Patients also completed the Patient‐Oriented Eczema Measure and quality‐of‐life measures. A Mexameter was used to measure baseline melanin indices. Ten random patients were rescored to test intrarater reliability. Results: We included 11 light‐skinned patients (melanin index ≤ 200) and 14 patients with SOC (melanin index > 200) in the cohort. The inter‐rater intraclass correlation coefficients (ICCs) were EASI 0·83 [95% confidence interval (CI) 0·66–0·94] for light skin and 0·77 (95% CI 0·60–0·91) for SOC; oSCORAD 0·68 (95% CI 0·44–0·88) for light skin and 0·74 (95% CI 0·54–0·89) for SOC; and IGA 0·80 (95% CI 0·62–0·93) for light skin and 0·70 (95% CI 0·49–0·87) for SOC. The greyscale had an ICC of 0·78 (95% CI 0·60–0·91) when replacing the EASI's erythema scale for patients with SOC. All scores showed excellent intrarater reliability for all skin types. Erythema component analysis showed that erythema did not contribute to variability. Conclusions: EASI showed excellent reliability for patients of all skin colours, and is recommended as the optimal core measure for patients with all skin colours. Abstract : What's already known about this topic? The Eczema Area and Severity Index (EASI) has been recommended as the core outcome measure for the clinician‐rated severity of atopic dermatitis (AD). AD in patients with skin of colour (SOC) is more difficult to assess because erythema may be less noticeable. There is a paucity of participants with SOC in AD clinical trials. The validity of existing severity outcome measures in SOC is not known. What does this study add? EASI has demonstrated excellent inter‐rater and intrarater reliability for patients of all skin colours, supporting it as the core outcome measure for AD clinical trials for patients with or without SOC. Contrary to our prior expectations, erythema perception did not contribute to inter‐rater variability in patients with SOC. Patients with SOC may perceive their AD symptoms as less severe than their light‐skinned counterparts. What are the clinical implications of this work? From these results we recommend the EASI score to be used a core measure in all AD clinical trials for patients of all skin colours. We strongly advocate for the inclusion of patients with SOC in future AD clinical trials. Respond to this article Linked Comment:Chansky et al. Br J Dermatol 2017;176 :853–854 Plain language summary available online